INFLUENCE OF IRRIGATION LEVELS AND INTEGRATED WEED MANAGEMENT ON GROWTH AND YIELD OF AEROBIC RICE (Oryza sativa L.) - T. RAMESH, S. SRINIVASA RAO, K.B. SUNEETHA DEVI, M. MADHAVI, T. RAM PRAKASH and (The Journal of Research, PJTSAU, 2017)
The experiment was conducted to study the influence of four irrigation levels (IW/CPE ratios of 0.5, 1.0, 1.5 and 2.0) and six integrated weed management practices of application of pendimethalin/butachlor @ 1.0 kg ha-1 as PE fb fenoxyprop-p-ethyl @ 60 g ha-1 at 15 DAS and metsulfuron methyl + chlorimuron ethyl @ 4.0 g ha-1 as post emergence herbicides followed by MW + HW at 45 DAS, weed free check and unweeded control on growth and yield of aerobic rice. The results revealed that higher growthparameters (plant height, tillers m-2 and dry matter production) at harvest and grain yield, straw yield and harvest index were recorded by irrigations given at IW/CPE ratios of 2.0 and 1.5 over other irrigation levels (0.5 & 1.0) and among weed management practices weed free check, application of pendimethalin/butachlor @1.0 kg ha-1 as PE fb metsulfuron methyl + chlorimuron ethyl @ 4.0 g ha-1 at 25 DAS + MW fb HW at 45 DAS were the best practices and followed to this pendimethalin/butachlor @ 1.0 kg ha-1 applied as PE fb fenoxyprop-p-ethyl @ 60 g ha-1 at 15 DAS fb MW + HW at 45 DAS recorded lower but higher than unweeded control. Combination of irrigation level at IW/CPE ratio of 2.0 along with weed free check and same level of irrigation (2.0) along with pendimethalin/butachlor @ 1.0 kg ha-1 applied as PE fb metsulfuron methyl + chlorimuron ethyl @ 4.0 g ha-1 at 25 DAS fb MW + HW at 45 DAS recorded higher yields and harvest index during kharif 2013, 2014 and pooled mean.